"Hey, Have You Been Tested?" The Influence of Comprehensive or Abstinence-Only Sexuality Education on Safer Sex Communication and Behavior. Issue 2 (3rd April 2021) - Grasso, Katherine L.; Trumbull, Lauren A.
Abstract: This study explored how sexuality education relates to young and emerging adults' sexual behavior and communication. A questionnaire measured 140 U.S. participants' (18–28) school-based sexuality education, age at sexual debut, birth control use, relationship with recent sexual partner, and safer sex communication (SSC) during their last encounter. Those who underwent abstinence-only sexuality education began having sex a year later than those who had comprehensive sexuality education. Contraceptive use did not differ across sex education type. Overall, respondents reported high levels of SSC, with minimal differences in SSC across sexuality education types. Implications for sexuality education and SSC training are discussed.